Ergonomic Study in Developing The Organizational Culture to Improve SME's Performance - Nurwildani, Mohammad Fajar; Purnomo, Hari; Soewardi, Hartomo; Kusrini, Elisa (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
In industrial companies, both large and small-scale, performance is the main indicator of organizational success. Optimal performance can be achieved if the organization implements a healthy and effective organizational culture. On the contrary, an improper organizational culture can lead to conflicts between employees and stakeholders. Conflicts often arise that can cause work discomfort. The impact is to reduce work morale, negatively impacting performance and leading to a decline. Therefore, organizations need to build a culture that considers the human factor. One approach that can be applied is the concept of ergonomics, which integrates physical, cognitive, and organizational aspects to create a comfortable work environment so that employees can work healthily and effectively. This study aims to analyze the role of ergonomics on organizational culture and its implications in improving worker performance in the SME environment. This study uses a quantitative approach, supported by field observations and structured interviews with workers and managers of SMEs. Data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of the study show that ergonomic aspects that have a significant effect on the formation of organizational culture with a loading factor value greater than 0.7 include physical ergonomics through workload variables (with work duration indicators), work environment variables (with temperature, humidity, lighting, and noise indicators), and equipment and equipment variables (with indicators of tool and machine design conditions, cognitive ergonomics (with indicators of perception, logical reasoning, and working relationships); and organizational ergonomics through work system design variables (with communication indicators and task variations) and work organization variables (with organizational structure indicators). These findings confirm that improving ergonomics not only creates a healthier and more efficient work environment but also strengthens organizational cultural values, which ultimately positively impacts the overall performance of SMEs